Replication data for: Correlations between modest weight loss and leptin to adiponectin ratio, insulin and leptin resensitization in a small cohort of Norwegian individuals with obesity. - Isaksen, Victoria Therese; Larsen, Maria Arlén; Goll, Rasmus; Paulssen, Eyvind Jakob; Florholmen, Jon (DataverseNO, 2019)
The present dataset is the basis of the results presented in "Modest weight loss improves leptin to adiponectin ratio and induces insulin and leptin resensitivization in individuals with obesity." (manuscript submitted 2019, December). Please read the accompanying ReadMe file for a further description of variables. Abstract: Background: Identifying patients at the highest risk of adverse consequences of obesity is of great importance in order to better monitor the effects of treatment. This study aims to investigate whether dysregulated adipokines and postprandial triglycerides (TG) improve with modest weight loss. Methods: Individuals with obesity were recruited by posters, among patients at the University Hospital of North Norway and the Stamina Health weight loss program. We calculated the Homeostasis Model Assessment of Insulin Resistance (HOMA-IR), leptin to adiponectin (L:A) ratio, indirect leptin sensitivity (REE:leptin ratio), postprandial TG clearance at 6 h and TG response from samples collected at visits before and after weight loss. The weight loss goal was ≥5% of initial total weight. Results: Twenty-eight participants attended both assessments, of which 13 lost ≥5% body weight. Of these, five lost ≥10% body weight. HOMA-IR (-23.1%), REE:leptin ratio (+80.1%) and L:A ratio (-45.7%) significantly improved with a weight loss ≥5%, whereas there was no improvement of postprandial TG response or clearance. Participants with ≥5% weight loss improved their L:A ratio over cut-off values ≥1.88 and ≥2.2 significantly, and participants with ≥10% weight loss improved their L:A ratio over the cut-off value ≥3.65 significantly. Participants with ≥10% weight loss also improved their HOMA-IR over cut-off value ≥2.3 significantly. Conclusion: Metabolic dysregulation measured by the surrogate biomarkers HOMA-IR, REE:leptin ratio and L:A ratio, but not postprandial TG, improve with a modest weight loss of ≥ 5%. Further improvements in these biomarkers are seen in weight loss of ≥10%. To measure postprandial TG ...